Proton-pump Inhibitors and the Risk of Dementia: A Systematic Review and Meta-analysis - Kyu-Tae Yoon; Chang Seok Bang; Joon Sung Kim (Yong Chan Lee, 2021)
Background/Aims Proton pump inhibitors (PPIs) are widely used to treat several acid-related gastrointestinal disorders. This study aimed to investigate the risk of dementia in patients taking PPIs. Materials and Methods A systematic review was conducted to evaluate the correlation between PPIs and dementia. The methodological quality of the included studies was evaluated using the Risk of Bias Assessment tool for non-randomized studies. Publication bias was assessed. Results A total of 12 nested, case-control, and cohort studies were identified and analyzed. We obtained hazard ratios (HRs) from five studies and performed a meta-analysis. The meta-analysis of four cohort studies and one nested case-control study showed no association between PPIs and dementia (HR, 1.165; 95% CI, 0.912~1.488; P=0.222). Sensitivity analysis revealed consistent results. No publication bias was detected. Conclusions This systematic review and meta-analysis revealed no statistically significant association between the use of PPIs and dementia.